2018
DOI: 10.1159/000495589
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Circular RNA Profiling Reveals the Regulatory Role of the CircRNA-0067835/miR-155 Pathway in Temporal Lobe Epilepsy

Abstract: Background/Aims: Temporal lobe epilepsy (TLE) is the most common form of adult localization-related epilepsy that is accompanied by progressive etiopathology and high incidences of drug resistance. Circular RNAs (circRNAs) play important roles in fine-tuning gene expression, however, the expression profile and clinical significance of circRNAs in TLE remains unknown. Methods: Circular RNA microarray was conducted to identify TLE-related circRNAs. CCK8 assays and flow cytometric assays were conducted to clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…S4). Another mechanism by which miRNA function can be reduced is via circular RNA (circRNA), which binds specific miRNAs rendering the bound miRNAs inactive, and studies have found circRNA levels to be altered in epilepsy (66). Adjustment of criteria for selecting miRNAs could yield additional miRNAs for functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…S4). Another mechanism by which miRNA function can be reduced is via circular RNA (circRNA), which binds specific miRNAs rendering the bound miRNAs inactive, and studies have found circRNA levels to be altered in epilepsy (66). Adjustment of criteria for selecting miRNAs could yield additional miRNAs for functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous reports suggesting the potential role of circRNAs as biomarkers or therapeutic targets in neurological conditions, such as multiple sclerosis or epilepsy, have been already published [29][30][31]. In the stroke field, a number of changes in circRNAs expression levels have been recently described.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAs identified in humans, animals, plants (including Arabidopsis, rice, and soybean), and yeasts (Saccharomyces cerevisiae and Schizosaccharomyces pombe) [31][32][33][34][35] can serve as sponges of miR-NAs and regulate the expression of parental genes [14,22,36,37]. The roles of circRNAs have been reported in various diseases including diabetes and many vascular diseases [38,39]. Particularly, some studies have identified the functions of certain circRNAs in vascular endothelial cells induced by hypoxia or other inducers [40][41][42].…”
Section: Discussionmentioning
confidence: 99%